DETERMINAN MENYUSUI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS NGAWEN KECAMATAN NGAWEN KABUPATEN BLORA - Kusnadhi, Froulien Ni'mah; Susiloretni, Kun Aristiati (Poltekkes Kemenkes Semarang, 2016)
Background : Breast milk (ASI) contains all the nutrients a baby needs and contains antibodies. Exclusive breastfeeding can prevent a variety of diseases and can reduce infant mortality. Scope of exclusive breastfeeding in the Ngawen public health center of 42.4%, still lower than the national Minimal Standard Service is 80%. There are determinant factors associated with the success of breastfeeding is exclusive. Methods : Explanatory with cross sectional design. Sampling was systematic random sampling method interval to get a sample of 204 mothers breastfeeding babies 0 - 6 months. Data collected included age, education, parity, employment status, knowledge, attitudes, ways of bonding, difficulty breastfeeding, support her husband, grandmother support, IMD, support health workers, received a package formula, support cadre and access to the formula, obtained using questionnaire with interview. Analysis analytic using chi-square test and Fisher's correlation exact. Results : Factors associated with exclusive breastfeeding is the knowledge (p value 0.000), attitude (p value 0.000), employment status (p = 0.000), difficulty breastfeeding (p = 0.000), the support of her husband (p = 0.000), grandmother support ( p value 0.000), IMD (p = 0.002), the support of health workers (p = 0.047) and access to the formula (p = 0.012). Conclusion: There is a significant relationship between knowledge, attitudes, employment status, difficulty breastfeeding, support her husband, grandmother support, IMD, support health workers and acces to the formula with exclusive breastfeeding.